Historicizing translation as (de)colonial practices: China's 1867 debate on learning western sciences as an example. Issue 3 (4th May 2022) - Zhao, Weili
ABSTRACT: This paper examines translation as a political-textual-epistemological battlefield of colonialism-coloniality and counter wise, which construes and constructs day-to-day communications/confrontations between people both within and across empires. It examines the Tongwen Guan 1867 debate on calling on prospective Confucian scholars to learn Western sciences as an eventful site of such translational practices. Reading into the Qing memorial texts and foreign ministers' dispatch reports, this paper historicizes the ways in which the epistemic debate translingually entangles Sino-West power (dis)ordering, Qing China's inner confrontations among the literati officials, and the colonial expansion of Missionary gospels. Situated within the historical and epistemic contexts, the analysis explicates a dao-qi episteme that trans-orders Chinese and western sciences, a yi/barbarian framework that trans-orders (un)worthy teachers, and a 'China origin' trope that ultimately endorses western learning in modern China. As a case study, this paper provides implications for explicating cultural-epistemic differences through translingual practices as a de-colonial gesture.